2021
DOI: 10.1016/j.cegh.2021.100855
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of malnutrition associated with chronic kidney disease patients globally and its contrast with India: An evidence based systematic review and meta-analysis

Abstract: Background: Malnutrition is one of the most serious complications of chronic kidney disease due to its devastating consequences in terms of quality of life, morbidity, hospitalization and mortality. This study aims to evaluate the prevalence of malnutrition among chronic kidney disease patients globally and its contrast with India. Methods: Articles reporting the prevalence of malnutrition associated with CKD patients were retrieved from PubMed/Medline, ScienceDirect, Cochrane library & Google scholar. The qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
1
12
1
1
Order By: Relevance
“…[22][23] Regarding gender dominance, male cases had higher malnutrition than females but not significantly different, it is consistent with a recent Indian study. [24] A worse quality of life, sleep disorders, depression, hyporesponsiveness to erythropoietin, greater susceptibility to infections, and worsening of heart failure are all potential outcomes of malnutrition. [25][26][27][28] As a result of the findings of this research, which demonstrated that malnutrition begins at an early stage in the progression of CKD, there is reason for including nutritional evaluation as part of the management of CKD patients even in the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23] Regarding gender dominance, male cases had higher malnutrition than females but not significantly different, it is consistent with a recent Indian study. [24] A worse quality of life, sleep disorders, depression, hyporesponsiveness to erythropoietin, greater susceptibility to infections, and worsening of heart failure are all potential outcomes of malnutrition. [25][26][27][28] As a result of the findings of this research, which demonstrated that malnutrition begins at an early stage in the progression of CKD, there is reason for including nutritional evaluation as part of the management of CKD patients even in the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Poor nutritional status or malnutrition is an under-recognized and undertreated condition that has a high clinical impact on patients across different healthcare settings [10][11][12]. Patients with chronic renal disease frequently have this complication [13,14]. According to the available research, there is a clear connection between poor nutritional status and morbidity, the geriatric population, and gender [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition shares a strong bond with the renal outcomes. India has reported a huge prevalence of malnutrition (56.7%) among chronic kidney disease patients [13]. The prevalence of malnutrition, however, varies depending on the stages of CKD, gender, and dialysis status [19].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, India occupies the third position in malnourished CKD patients with a pooled prevalence of 56.7%, among hemodialysis, peritoneal dialysis, and nondialysis CKD. 1 , 2 Even so, predialysis CKD patients are an understudied population as compared to hemodialysis in the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%